Controllable synthesis of Fe3O4-based magneto-dielectric ternary nanocomposites and their enhanced microwave absorption properties. (9th October 2020) - Liu, Juncen; Yang, Zhihong; Li, Meng; Yang, Lieji; Xue, Tong; Xu, Guoyue
Abstract: In order to overcome the drawbacks of Fe3 O4 composite samples and greatly increase their performance in microwave absorption, magnetic Fe3 O4 spindles coated with dielectric SnO2 nanorods and MnO2 nanoflakes have been successfully synthesized by a four-step simple hydrothermal route. This rationally designed magneto-dielectric ternary nanocomposite will introduce multiple reflection and conductive losses caused by its special multilayer structure and the effective complementarity of dielectric loss and magnetic loss. Therefore, its absorbing performance can be greatly improved. It is notable that the as-prepared Fe3 O4 @SnO2 @MnO2 nanocomposites show a minimum reflection loss value of −50.40 dB at 17.92 GHz at a thickness of 3.9 mm and the absorption bandwidth ranges from 3.62 to 12.08 GHz. The as-prepared Fe3 O4 @SnO2 @MnO2 ternary nanocomposite is expected to be a potential candidate for high-performance microwave-absorbing materials with intensive electromagnetic wave absorption and wide effective absorbing bandwidth.